A Technical Note: On Niosomes - Vrunda, Rajput J.; Anuja, Gawai G.; Rupali, Sable P.; Subodh, Urkunde A.; Sandeep, Atram C. Dr. (Asian Journal of Pharmaceutical Research and Development, 2024)
A wide range of substances that serve as carriers can be suspended or captured by the Niosomes Delivery System (MDS), which can then be included into a designed product like a gel cream or powder. The formulation's primary goal is to get the desired medication concentration in the blood. Niosomes are a type of porous medication delivery device for small particles. They are tiny, spherical particles that resemble microscopic and have a broad porous surface. In addition, they may increase stability by altering the drug's release pattern while minimizing negative effects. The serious condition impacting social life is acne vulgaris. Acne can be involved; alternation of follicular keratinization seldom causes significant systemic issues, but maturity, especially for women, which leads to drugs assist to reduce the production of sebum, which is mostly responsible for reducing the formation of acne on the skin. The use of niosomes as carriers for medications that target acne vulgaris is currently receiving more attention in research that focuses on illness detection and a brief to target acne vulgaris. Acne vulgaris is a serious condition that is currently affecting people's social lives. Increased sebum production, bacterial involvement, altered follicular keratinization, and altered follicular barrier are all characteristics of acne. The current review is focused on the niosomes as carriers for the drug targeting the acne vulgaris, brief discussion on the present and future aspects of the niosomes to targetet acne vulgaris.